Infância e relações de cuidado na escola pública de tempo integral - Aline Regina Gomes (2019)
The aim of the thesis was to understand caring in a full time public school in Belo Horizonte-MG, analyzing the phenomenon in a dynamic of relationships, both interpersonal and institutional. The theoretical framework was situated in the interdisciplinary dialogue of Care, Childhood and Education Studies, seeking for concepts and theories articulations. The main methodological choices were based on qualitative research, taking ethnography as the researcher guide to the empirical data construction. Also, the participant observation was the main ethnographic instrument and semi-structured interviews were conducted as an additional methodological strategy. Ethical care procedures were followed as recommended by national agencies. The research field was conducted throughout 2017 school year at a full-time municipal public school located in Ribeiro de Abreu. The six-year-old class (first year of Elementary school) and their educators were the most direct collaborators in the research. Throughout the analyzes, we listed axes and analytical categories as a more systematic form of data organization. The axes, as major themes that drove the empirical discussion, were 'time', 'body' and 'generation'; while categories, once more specific, were 'care practices', 'play' and 'territory'. The study showed that care relationships are present in various ways in the observed context. Care practices are mediators of adult action, producing places in the institution and performed in association with the real children participation in care. As dimensions of human life, caring and being cared for demanded a school time, which often mixed with the time of playing in school. In addition, care relationships were not restricted to the limits of school space. The children brought questions from the home world to the school, which in turn welcomed such questions. From the concept of 'care network', I demonstrate how the school is central, dialogues with the territory and articulates other subjects and institutions in the processes of child care. Thus, the visibility of the care that the present work set out to do brought the need for such discussion in the context of Elementary Education as a whole, even when linked to full-time proposals from the perspective of Integral Education. It is a debate where the heart of the matter is caring as a school task: an educational task understood in the light of the formation and humanization of the subjects.